(3GdefJbi aj GdCMcGe Yf NjQ GdCfGe eMeO Ydjg CaVd GdUdGI hGdSdGes - (3YHO GdSdGe Hf YHO Gddg Hf GdNVQ Hf eMeO, GHf JjejI GdMQGfj, CHh GdHQcGJ, eLO GdOjf (B[ (3LO GHf JjejI (B](3,J (B652 (3g` s ((3eOjfI UfYGA s)
(3ChdgG (B:s
(3GdMeO ddg GdPi de jJNP hdOkG gPG cJGH jTJed Ydi LedI ef GdCMGOjK GdfHhjI GdJi JQLY CUhd GdCMcGe EdjgG s
(3BNQgG (B:s
(3ef SQJg MSfJg , hSGAJg SjFg , aPdc GdeDef QhGg CMeO hGdJQePi BNQ GdcJGH hGdMeO ddg hMOg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ GdCHhGH ajgG HGdMeQI s
(3Ydi GdfSNI JbjjOGJ cKjQI s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
Keywords: (3GdMOjK h GdeUWdMs